2012
DOI: 10.1017/s1041610212000762
|View full text |Cite
|
Sign up to set email alerts
|

Illness burden and symptoms of anxiety in older adults: optimism and pessimism as moderators

Abstract: Bolstering positive and reducing negative future expectancies may aid in the prevention of psychological distress in medically ill older adults. Therapeutic strategies to enhance optimism and reduce pessimism, which may be well-suited to primary care and other medical settings, and to which older adults may be particularly amenable, may contribute to reduced health-related anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…It uses a five-point Likert-type scale, with higher scores indicating higher levels of optimism. This scale has demonstrated good reliability in research involving older adults, with Cronbach's alpha ranging from 0.67 [24] to 0.75 [25]. Cronbach's alpha for the LOT-R in the current study was 0.68, with an inter-item correlation of 0.27 indicating good item homogeneity [26].…”
Section: Resistance Factorsmentioning
confidence: 50%
“…It uses a five-point Likert-type scale, with higher scores indicating higher levels of optimism. This scale has demonstrated good reliability in research involving older adults, with Cronbach's alpha ranging from 0.67 [24] to 0.75 [25]. Cronbach's alpha for the LOT-R in the current study was 0.68, with an inter-item correlation of 0.27 indicating good item homogeneity [26].…”
Section: Resistance Factorsmentioning
confidence: 50%
“…IN-OT produced stronger effects on less socially adapted individuals, such as those with high trait anxiety (34), impaired emotion regulation (35), or low emotional sensitivity (36). Because optimism has been implicated in anxiety and depression (26,27,37,38), we further examined whether the effects of IN-OT on optimistic belief updating were moderated by individuals' depression and anxiety traits. Given the finding of stronger effects of IN-OT on less socially adapted individuals (34)(35)(36), we hypothesized that IN-OT would produce stronger effects on belief updating in individuals with high (relative to low) depression and anxiety traits.…”
Section: Significancementioning
confidence: 99%
“…Research into gratitude has found that it can mitigate the risk of financial strain leading to depressive symptoms amongst older adults (Krause, 2009), and for those who are depressed, it can buffer the association between increasing depressive symptoms and suicidal ideation (Kleiman, Adams, Kashdan, & Riskind, 2013). Similarly, optimism has been found to confer resilience against the development of anxiety in the face of illness burden amongst older adults (Hirsch, Walker, Chang, & Lyness, 2012), and to buffer the likelihood that both chronic and acute life stressors will increase depressive symptoms amongst disadvantaged women (Grote, Bledsoe, Larkin, Lemay, & Brown, 2007). Trait hope has been found to buffer against the association between stressful life events and depression when measured cross-sectionally (Visser, Loess, Jeglic, & Hirsch, 2013) and daily stressors and negative affect in a diary study (Ong, Edwards, & Bergeman, 2006).…”
Section: Symptoms Of Psychological Disordermentioning
confidence: 99%